Characterization and phenetic analysis of geographical isolates of Beauveria spp. - Gómez, Danile Ricardo Sosa; Alves, Sérgio Batista; Milani, Myrian Tigano (Pesquisa Agropecuaria Brasileira, 1994)
Nine pathotypes of Beauveria bassiana (Bals.) Vuill. and one pathotype of B. brongniartii (Sacc.) Petch were characterized according to extracellular enzyme production, growth rate on different culture media, conidial dimensions, conidiogenesis in vitro, isoenzyme variation, and virulence toward Diatraea saccharalis. Biological differences were found among isolates; only one isolate showed lipolytic activity. Two isolates had limited growth at three levels of temperature. LT50 values ranged from 5.9 days (virulent) to more than 8 days (non virulent). Electrophoretic analysis from a and b - esterases were performed to differentiate isolates. Pairwise coefficients of similarity calculated from these parameters were used to construct phenograms in order to estimate the phenetic distance among the various fungal pathotypes. Isolates from the same regions had high coefficients of similarity, suggesting commonality within geographic populations.